Faktor-Faktor Yang Ada Hubungan Dengan Ibu Yang Melahirkan Bayi Berat Badan Lahir Rendah Di RSUD dr. La Palaloi Periode Januari 2023 - Mirnawati, Mirnawati; Hasbullah, Ayu Ameliyah; Hariadi, Anisyah (Fakultas Kedokteran Universitas Bosowa, 2025)
Low Birth Weight is caused by short gestational age (prematurity), IUGR (Intra Uterine Growth Rection) or stunted fetal growth. Both of these causes are influenced by maternal and fetal risk factors. Both of these factors lead to reduced nutritional intake of the fetus during pregnancy. These risk factors cause a lack of fulfillment of nutrition in the fetus during pregnancy. The purpose of this study was to determine risk factors for low birth weight (1) age (2) parity (3) nutritional status (4) gemelli pregnancy (5) prenatal check-up (ANC). This research was conducted on 40 mothers giving birth at dr. La Palaloi for the period January 1 2023 to January 31 2023. This study used an analytic observational method with a case control study design using primary data in the form of interviews with mothers who gave birth to low birth weight babies at dr. La Palaloi for the January 2023 period. Data analysis was processed using SPSS software. The results of this study indicate the risk factors for mothers giving birth to low birth weight babies at Dr La Palaloi General Hospital for the January 2023 period, namely: (1) Obtained a relationship between age and mothers who gave birth to low birth weight babies, (2) Obtained a relationship between parity and mothers who gave birth to low birth weight babies, (3) found a relationship between nutritional status and mothers who gave birth to low birth weight babies, (4) found a relationship between gemelli pregnancies and mothers who gave birth to low birth weight babies, (5) found a relationship between pregnancy (ANC) with mothers who gave birth to babies with low birth weight. The conclusion of the study was that age, parity, nutritional status, pregnancies and pregnancy checks (ANC) were risk factors for mothers giving birth to low birth weight babies at RSUD dr. La Palaloi period January 2023.